Optimizing the Role of Other Patient's Families in Injury Prevention in Fall Risk Patients - Mohammad Henri Wahyono; Mury Ririanti (Health and Technology Journal (HTechJ), 2023)
There are still incidents of patients falling while undergoing treatment at health facilities, requiring us as officers to look for various prevention efforts, improve patient safety support facilities, and involve all patient caretakers' families to jointly care for patients around them who are at risk of falling. This study aims to see efforts to optimize the role of other families in preventing the risk of falling. This type of research is qualitative, involving eight main informants from the head of the room and eight additional informants from the families of waiting for patients at RSUD Dr. H. Koesnadi Bondowoso. This research was conducted from 26 February to 24 March 2023 by collecting data through unstructured interviews, in-depth observation, and documentation studies. The data obtained was verified by triangulation of sources and techniques. The conclusion shows that efforts to prevent the risk of falling by optimizing the role of the patient's family are very effective because the patient's family feels happy by paying attention to the presence of patients around them, especially those wearing yellow marker bracelets so that the presence of the waiting family besides paying attention to the patient's family can also take a role by paying attention to other patients surrounding.